Knowledge, Attitudes and Practices Regarding Gestational Diabetes Mellitus Among Pregnant Women - A Cross-Sectional Study - Durghashree C; Sarojini .; Prathima S; Meghana C (RGUHS National Journal of Public Health)
nbspBackground Gestational diabetes mellitus GDM a major health concern often results in poor maternal and neonatal outcomes. Understanding the knowledge attitudes and practices of patients towards GDM is crucial for improving self-management and reducing complications.Objectives To assess the knowledge levels among pregnant women regarding GDM its risk factors symptoms complications and management to assess the attitudes of pregnant women towards GDM screening diagnosis and treatment to evaluate the practices adopted by pregnant women for preventing managing and coping with GDM and to understand the dietary habits physical activity and adherence to medical recommendations in these women.Methodology This study was conducted for a period of 12 months at a teaching institute in Bangalore. A total of 174 pregnant women diagnosed with GDM were included. The participants completed a validated KAP questionnaire assessing their knowledge 18 questions attitudes 8 questions and practices 10 questions regarding GDM.Results The mean knowledge score was 5plusmn3.04 out of a total possible score of 18 indicating poor awareness of GDM among participants. Attitude scores were moderate with a mean of 18plusmn5.3. The mean score in the practice section averaged 8plusmn2 out of a total possible score of 16. In all the three KAP sections the scores were significantly influenced by socioeconomic status method of conception and history of polycystic ovary syndrome PCOS.Conclusion This study highlights the poor knowledge moderate attitudes and practices among GDM patients in a resource-limited setting. Educational programs tailored to the needs of these women are essential for improving self-management and reducing GDM-related complications.